2007
DOI: 10.1039/b711174f
|View full text |Cite
|
Sign up to set email alerts
|

Contact angles in relation to emulsions stabilised solely by silica nanoparticles including systems containing room temperature ionic liquids

Abstract: We report measured and calculated oil-ionic liquid, water-ionic liquid and oil-water contact angles on silica surfaces which have been hydrophobised to different extents by silanisation. Based on the idea that the contact angle formed by a liquid-liquid interface with a particle adsorbed at that interface is a key determinant of the strength of particle adsorption and the tendency of the adsorbed particle film to curve, we correlate the contact angle data with the phase inversion points and stabilities of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…Compared with the complicated situation of IL electrowetting in GLS systems, research for electrowetting in LLS systems is much clearer. Being different from the electrowetting behavior in air, electrowetting by pure IL or IL–water solutions under another immiscible liquid is generally reversible with very low contact angle hysteresis, and the efficiency is significantly higher (Figure d,e) . From Equation , it is obvious that the key difference between GLS and LLS systems is γ , where the liquid/air surface tension is replaced by liquid/liquid surface interfacial tension.…”
Section: Electrowetting By Ionic Liquidsmentioning
confidence: 99%
“…Compared with the complicated situation of IL electrowetting in GLS systems, research for electrowetting in LLS systems is much clearer. Being different from the electrowetting behavior in air, electrowetting by pure IL or IL–water solutions under another immiscible liquid is generally reversible with very low contact angle hysteresis, and the efficiency is significantly higher (Figure d,e) . From Equation , it is obvious that the key difference between GLS and LLS systems is γ , where the liquid/air surface tension is replaced by liquid/liquid surface interfacial tension.…”
Section: Electrowetting By Ionic Liquidsmentioning
confidence: 99%
“…With a combination of many unique properties such as negligible volatility, non-flammability, thermal and chemical stability, and high ionic conductivity, as well as potential broad applications, increasing amounts of attention have been paid to ionic liquids, especially RTILs. 143,[171][172][173][174][175] The properties of RTILs can be varied from hydrophilic (i.e. water-miscible but immiscible with low polarity solvents (we use the term 'oil' here)) to hydrophobic (i.e.…”
Section: Novel Double Pickering Emulsions Of Room Temperature Ionic Lmentioning
confidence: 99%
“…[142][143][144] Based on a water-instyrene-in-water-in-styrene (W/O/W/O) triple Pickering emulsion stabilized by 3 wt% of 50% SiOH silica nanoparticles in the inner oil phase, and 2 wt% of the same silica type in the outer oil phase and oil globules, was stabilized by 2 wt% of 80% SiOH silica based in the second water phase, Dyab et al have gained a new porous hierarchical structure after the polymerization of the oil phase. 145 …”
Section: Hierarchical Porous Polymeric Microspheresmentioning
confidence: 99%
“…The problem is further complicated by the scarcity of information on IL interfacial properties. Recently, Binks and coworkers [14,15] observed that fumed silica nanoparticles successfully adhered to IL interfaces to stabilize a series of Pickering emulsions. Nakashima et al reported that polystyrene particles adhered to the IL/water interface and the self-assembled morphology could be modified by changing the water pH or IL composition [16].…”
Section: Introductionmentioning
confidence: 99%